Is God a delusion? : a reply to religion's cultured despisers - Reitan, Eric. (Oxford : Wiley-Blackwell, 2009)
"Is God a Delusion? addresses the philosophical underpinnings of the recent proliferation of popular books attacking religious beliefs. The book focuses primarily on charges leveled by recent critics that belief in God is irrational and that its nature ferments violence. It balances philosophical rigor and scholarly care with an engaging, accessible style, and offers a direct response to the crop of recent anti-religion bestsellers currently generating considerable public discussion."--BOOK JACKET.
On religion and equivocation -- "The God hypothesis" and the concept of God -- Divine tyranny and the goodness of God -- Science, transcendence, and meaning -- Philosophy and God's existence, part I -- Philosophy and God's existence, part II -- Religious consciousness -- The substance of things hoped for -- Evil and the meaning of life -- The root of all evil?
Includes bibliographical references (p. [234]-240) and index.
Keywords: God -- History of doctrines; Apologetics; Theism; Belief and doubt -- Cross-cultural studies